To worry or not to worry: breast cancer genetic counseling communication with low-income Latina immigrants - Joseph, Galen (J Community Genet, 2014)
The purpose of this pilot study was to describe communication practices during hereditary breast cancer genetic counseling (GC) with low-income immigrant Latina patients in a public hospital setting. We utilized qualitative ethnographic methods, including direct observation of GC appointments with Latina patients at a public hospital offering free GC and BRCA testing and in-depth qualitative interviews with patients after they had received their BRCA genetic test results. Twenty-five patients participated; 20 were observed during genetic counseling appointments, and ten participated in interviews after BRCA testing with six participating in both observations and an interview. Analyses of qualitative data from observation field notes and interviews identified both strengths and limitations of current communication practices within the following themes: (1) family health history communication, (2) education regarding genes and genetics and patient information needs, (3) the purpose of the genetic test, (4) genetic test results and cancer risk, (5) building rapport and providing support, and (6) medical interpretation for monolingual Spanish speakers. As access to cancer GC expands in the public safety net settings and for the diverse populations they serve, it is critical to ensure effective communication in order for patients, whether or not they have a BRCA mutation, to understand the nature of their cancer risk and recommended methods of screening and prevention. Intervention strategies that address both structural constraints and patient-provider communication are needed to improve GC communication with immigrant Latinas, especially monolingual Spanish speakers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12687-014-0202-4) contains supplementary material, which is available to authorized users.